Opowiadania wybrane - Orzeszkowa, Eliza, 1842-1910.; Orzeszkowa, Eliza, 1842-1910. (Rzeszow : KAW, 1992)
A collection of short stories by the noted 19th century Polish author.
Keywords: Short stories, Polish